Updated status of Nepal’s wetland birds - Baral, HS (Banko Janakari, 2009)
Wetland birds in Nepal comprise significant portion of avian fauna of Nepal. However, they are also highly threatened because of several factors. A thorough study on wetland bird communities is lacking which is hampering conservation of wetlands and bird communities dependent on them. Proper management of the wetland beyond the protected areas is essential to conserve wetland birds in Nepal. Key words: Wetlands, birds, threatened, management doi: 10.3126/banko.v19i3.2209 Banko Janakari, Special Issue February 2009, 30-35